A certification for natural wine? Comparative analysis of consumer drivers in Italy and Spain - Eva Parga-Dans; Riccardo Vecchio; Azzurra Annunziata; Pablo Alonso González; Raimundo Otero Enríquez (Wine Economics and Policy, 2023)
The 2020 certification of natural wine (NW) in France has unleashed a heated debate in Europe. However, knowledge about NW consumer profiles and preferences in a comparative perspective remains scarce in the academic literature. This study aims to define the perceptions, preferences and profiles of wine consumers who support a NW label. For this purpose, we employed analysis of variance, aprioristic factor analysis and multiple regression analysis to examine data from a direct survey performed in Italy and Spain in 2020. Findings reveal that NW consumers in both countries deem it necessary to establish a certification for NW. However, we found significant differences regarding consumers' profiles, as well as purchasing preferences. In Spain, demand for NW certification is linked to eco-healthy and proximity-craft attributes of wine, and is considered more important by non-professional consumers and those with lower educational level. In Italy, information on the label and the purchase experience are the most important factors to aid in recognizing NW, while women show a significant interest in the NW certification. These findings may help policy-makers to establish homogeneous parameters to differentiate and certify NW.
Keywords: 330; consumer preferences; food certification; eco-labels; natural wine; food labeling